The effect of watching political programs on islamic-based party political images among Muhammadiyah students - Ahyan Putra; Aiur Ochirov (International Journal of Communication and Society, 2020)
This study aims to know the effect of watching the Indonesia Lawyers Club political episode program against the image of Islamic-based political parties among the Muhammadiyah Students Association of UIN Sunan Kalijaga ahead of the 2019 Presidential Election. Theories used are Cultivation Theory, television watch intensity, political parties' image, and Islamic based political parties. Validity test uses criteria validity calculated using the Pearson Product Moment formula, while the reliability test uses the Alpha Cronbach formula with the help of SPSS version 15. The type of analysis of this research is quantitative descriptive research with survey methods and data analysis using inferential parametric statistical methods, namely, the Pearson Product analyses Moment with the help of SPSS version 15. Meanwhile, to find out the magnitude of the effect of watching television using the formula Coefficient of Determination. Data collection techniques using questionnaires, interviews, literature studies, and documentation with sampling techniques using random sampling, as many as 62 respondents. From the data processing, it was found that there was an influence between watching the Indonesian Lawyers Club program on political episodes on the image of Islamic-based political parties among the Muhamadiyah Students Association UIN Sunan Kalijaga before the 2019 presidential election. Other variables also influence the formation of the image of political parties. This study uses DK = 60 (N-2 or 62-2) and the level of probability or significance level of 0.05 (5%), then the table is 0.250, and from the calculation, the recount is 0.550. Thus, since counted tables, Ho is rejected, and Ha is accepted.